If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(x + 1) = 20 Reorder the terms: 5x(1 + x) = 20 (1 * 5x + x * 5x) = 20 (5x + 5x2) = 20 Solving 5x + 5x2 = 20 Solving for variable 'x'. Reorder the terms: -20 + 5x + 5x2 = 20 + -20 Combine like terms: 20 + -20 = 0 -20 + 5x + 5x2 = 0 Factor out the Greatest Common Factor (GCF), '5'. 5(-4 + x + x2) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(-4 + x + x2)' equal to zero and attempt to solve: Simplifying -4 + x + x2 = 0 Solving -4 + x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '4' to each side of the equation. -4 + x + 4 + x2 = 0 + 4 Reorder the terms: -4 + 4 + x + x2 = 0 + 4 Combine like terms: -4 + 4 = 0 0 + x + x2 = 0 + 4 x + x2 = 0 + 4 Combine like terms: 0 + 4 = 4 x + x2 = 4 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. x + 0.25 + x2 = 4 + 0.25 Reorder the terms: 0.25 + x + x2 = 4 + 0.25 Combine like terms: 4 + 0.25 = 4.25 0.25 + x + x2 = 4.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 4.25 Calculate the square root of the right side: 2.061552813 Break this problem into two subproblems by setting (x + 0.5) equal to 2.061552813 and -2.061552813.Subproblem 1
x + 0.5 = 2.061552813 Simplifying x + 0.5 = 2.061552813 Reorder the terms: 0.5 + x = 2.061552813 Solving 0.5 + x = 2.061552813 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 2.061552813 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 2.061552813 + -0.5 x = 2.061552813 + -0.5 Combine like terms: 2.061552813 + -0.5 = 1.561552813 x = 1.561552813 Simplifying x = 1.561552813Subproblem 2
x + 0.5 = -2.061552813 Simplifying x + 0.5 = -2.061552813 Reorder the terms: 0.5 + x = -2.061552813 Solving 0.5 + x = -2.061552813 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -2.061552813 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -2.061552813 + -0.5 x = -2.061552813 + -0.5 Combine like terms: -2.061552813 + -0.5 = -2.561552813 x = -2.561552813 Simplifying x = -2.561552813Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.561552813, -2.561552813}Solution
x = {1.561552813, -2.561552813}
| 2,1/4x3,1/3 | | 22=-16t^2+40 | | p=6(9R-2) | | 6x+5x+4(2x)= | | Y/6.5-3.9=2.1 | | 6(3-x)=-5(2x+9)+18 | | 4x-24=7x+9 | | 3+5=17 | | (14/6x)-(3/6x)=100 | | 2m+3w=104 | | 20x+15y=2600 | | 24x+2x+5=17 | | (14/6)x-(3/6)x=100 | | -20/1x6/5 | | 6x+4=3-(9x-8) | | 6x+14=16x-6 | | (my-5x)/3z=5y | | 8x-4x=72+16 | | logx=169 | | my-5x=5y(3z) | | 5=(-z+3) | | 4x^2+9y^2-16x+18y=11 | | 2x+x=25+2 | | 2x^2-8x+10=x^2+2x-6 | | 6m+8=2m+32 | | x^3-2x^2-5x-6= | | (7n-6)(n+7)=0 | | .948=.75x-ln(x) | | 20=67-f | | .948=.75x-lnx | | (3x-16)=x | | 13q-11q-q=12 |